Estudo da estabilidade dos orbitais naturais de transição - Dias, Nildo Loiola (1982)
Various wavefuncttons for the 4-eletron systems, Li -, Be and B+ are obtained. For each one of these wavefunctions the F operator is determined. The eigenfunctions of this operator, one-particle functions called Natural Transition Orbitals, represent the occupied orbitals of the eletrons. These orbitals are obtained for each operator F. A comparative study is then made of the stability of the Natural Transition Orbitals of s-type in relation to the corresponding Natural Spin Orbitals (eigenfuncttons of the first-order density matrix) from the corresponding wavefunctions.